Que nunca pensé, ni aspiré a que trujeses thesoros de las Indias. Aristocracy and Courtly Mediation Regarding an Extravagant Provision of the Viceroyalty of Peru (1686-1688) - Quirós Rosado, Roberto (Revista Complutense de Historia de América, 2022)
The Court spheres of the Spanish Monarchy offer different points of view to be studied, both in spaces and actors. Given its prestige and political ascendancy, the aristocracy was a key role in this microcosm. Sociability and interests converged on a horizon marked by the need to establish channels of mediation with royal officials in order to obtain the king’s grace. The figure of the nobiliary mediator, however, has been obscured by the constant appearance of agents linked to the councils. This study will examine this figure through the correspondence between Antonio Ramírez de Haro, Count of Bornos, and his relative Pedro Félix Joseph de Silva, Count of Cifuentes, during the years 1686 and 1688, which articulated a process of recruitment of wills to obtain the Viceroyalty of Peru for the latter. A dignity that, after being obtained from Charles II, would not become effective due to the geopolitical and personal extravagances of the viceroy-elect.
Keywords: Viceroyalty; aristocratic mediation; Charles II; Peru; 17th Century